Global Governance Brazilian Views from Cardoso to Lula / Visões brasileiras da Governança Global de Cardoso a Lula - Coutto, Tatiana (Mural Internacional, 2010)
International leaders from throughout the world have been advocating the development of new institutional rules that reflect the changes faced by the international system over the last twenty years. The way governments perceive the challenges and opportunities posed by global governance – defined as dynamic system of interaction among political players with varying interests that seek to devise rules that generate standards of behavior - may have strong influence on foreign policy strategies, and should be studied more carefully by academia. Drawing on institutionalist literature and primary sources, this article discusses how Brazilian views on governance have evolved since 1994, to what extent do Cardoso and Lula’s administrations actually differ on this matter, and how such differences affect the country’s role foreign policy. RESUMO Líderes internacionais pelo mundo afora têm defendido o desenvolvimento de novas regras institucionais que refletem as mudanças enfrentadas pelo sistema internacional nos últimos vinte anos. A forma na qual governos percebem os desafios e oportunidades colocados pela governança global – definida como um sistema dinâmico de interação entre atores políticos com interesses variados que buscam elaborar regras que gerem padrões de comportamentos – pode ter forte influência nas estratégias de política externa, e podem ser estudados com mais atenção pelos acadêmicos. Baseado em literatura institucionalista e fontes primárias, este artigo discute como as visões brasileiras da governança evoluíram desde 1994; em que medida as administrações de Cardoso e Lula de fato diferem neste tema; e como essas diferenças afetam o papel do país em política externa. Keywords: Global Governance, Brazil, Worldviews. Palavras-chave: Governança Global, Brasil, Visões de Mundo. DOI: http://dx.doi.org/10.12957/rmi.2010.5320